Dynamics of cytokine status of blood serum in adolescents with varicocele - S. V. Pichugova; Yu. G. Lagereva; Ya. B. Beikin (Медицинская иммунология, 2023)
Varicocele is a varicose dilation of pampiniform plexus veins in testicular gland, considered a special case of phlebopathy. With varicocele, there is impaired venous outflow via the left renal vein from the veins of testicular pampiniform plexus. Increased hydrostatic pressure leads to failure of the wall tone of the testicular vein, valvular venous insufficiency with dilation of the local venous system. Vasodilation requires integrity of endothelial layer, and its damage resulting from hydrodynamic stress is a trigger for development of an inflammatory response and production of cytokines. Pro-inflammatory cytokines have a pronounced damaging effect on endothelial cells, leading to endothelial dysfunction and chronic inflammation. Angiogenesis is an important characteristic of inflammatory disorders. Both inflammation and its controlling mechanisms employ many common factors, including IL-1β, IL-6, IL-8, TNFα. The purposes of our study were: to determine the dynamics of the pro- and anti-inflammatory cytokine levels, and VEGF contents in blood serum of adolescents with left-sided varicocele in order to assess the severity of inflammatory reaction of the vessels in the pampiniform plexus as well as prognosis of angiogenesis and remodeling of the testicular veins. We examined 100 adolescents with left-sided varicocele II-III degree and 30 adolescents without varicocele, who made up the comparison group. All adolescents (14 to 17 years old) underwent determination of IL-1β, IL-6, IL-8, TNFα, IL-4, IL-10, VEGF levels in blood serum at a frequency of 1 year, depending on the degree of varicocele, terms after varicocelectomy.Statistically higher levels of pro-inflammatory cytokines were found over different age periods in adolescents with varicocele, as well as increased levels of anti-inflammatory cytokines, which may suggest an inflammatory process in testicular veins associated with varicocele. Higher levels of pro-inflammatory cytokines were found in patients with grade III varicocele compared with patients with grade II condition, but without statistically significant differences. In adolescents prior to varicocelectomy, significantly higher levels of cytokines were determined, which persisted over the postoperative period. Based on these results, one may assume that, in phlebopathy, the inflammatory process persists until surgical correction, and adaptation to the changed blood flow after surgery does not take time. VEGF values remain approximately similar over the observation period, and, probably, the changes of the vessel walls occur due to inflammatory process, and not to activation of angiogenesisIn varicocele disorder, an inflammatory status is observed in the altered testicular venous plexus, being more pronounced in grade III varicocele and affected by subsequent surgical correction.